Perioperative Short-Term Outcome in Super-Super-Obese Patients Undergoing Bariatric Surgery - Anna Dupree and Alexander Tarek El Gammal and Stefan Wolter and Silvana Urbanek and Nina Riedel and Oliver Mann and Philipp Busch (Obesity Surgery, 2018)
Background Prevalence of obesity is increasing with a pandemic magnitude worldwide. Incidence of super-super-obesity (>?60 kg/m2) is expanding by the same means. While bariatric surgery is the only approach with proven long-term results, surgical outcome in super-super-obesity is still discussed controversially. Objective This retrospective study examined bariatric surgery patients’ short-term outcome in relation to their degree of obesity. Setting Data collection was performed in a German university medical center between March 2010 and November 2013. Methods This study analyzes a cohort of 715 patients in a single institution. Patients were subdivided into three groups, obese (??49.9 kg/m2), super-obese (??50 kg/m2), and super-super-obese (??60 kg/m2), and evaluated regarding perioperative outcome. Results Three hundred eighty-one patients were included into obese (O); 225 patients, into super-obese (SO); and 109 patients, into super-super-obese (SSO) cohort. There were no significant differences regarding patient characteristics including quantity of comorbidities and perioperative outcome. BMI was significantly lower in patients with complications, compared to patients without complications (p?<?0.05), whereas patients’ age was significantly higher (p?<?0.05) in complication cohort. One SSO patient died of a septic multiorgan failure. Thus, the 30-day overall mortality was 0.14%. The BMI showed an inverse correlation to the patients’ age at surgery (p?<?0.05). Conclusion Super-super-obesity should not be considered as a limiting factor for bariatric surgery outcome; however, the patients’ age, surgeries prior to the bariatric procedure, and comorbidities must be considered prior to bariatric surgical treatment.